Extrapolating the susceptibility of Eld’s deer (Rucervus eldii thamin) to chronic wasting disease from prion protein gene (PRNP) polymorphisms - Perrin-Stowe, Tolulope I.N.; Ishida, Yasuko; Reed, Dolores M.; Terrill, Emily E.; Ryder, Oliver A.; Novakofski, Jan E.; Mateus-Pinilla, Nohra E.; Pukazhenthi, Budhan S.; Roca, Alfred L. (Frontiers in Conservation Science, 2022)
Chronic wasting disease (CWD) is a prion disease of North American cervids. The transmission of CWD to endangered cervid species is of concern for captive breeding programs. Trans-species transmission could occur via direct contact with infected wild deer, or via prion contaminated fomites. Variation in the prion protein gene, PRNP, is associated with differences in CWD susceptibility among cervids. We therefore sequenced PRNP in 36 endangered Eld’s deer (Rucervus eldii thamin), detecting five synonymous and two non-synonymous SNPs. Three haplotypes were inferred, suggesting that genetic management in captive breeding programs has been effective at maintaining PRNP diversity. The haplotypes encoded two PrP protein variants. The more common Eld’s deer PrP variant encodes methionine at codon 208 and glutamine at codon 226. Because this protein variant is identical to a common PrP variant in white-tailed deer and mule deer and is especially common in white-tailed deer positive for CWD, we recommend reducing the frequency of this variant in the breeding stock, while implementing strict management practices to avoid exposure to wild North American cervids. The frequency of the other PrP variant, which differs from variants present in these North American cervids, was low. It has the potential to reduce susceptibility to CWD and thus could be increased in frequency. While PRNP haplotype frequencies should be shifted, genetic diversity should be maintained. Ultimately protein diversity may be protective should CWD infect the species, and trans-species polymorphisms are suggestive of past balancing selection and a potential fitness advantage for PRNP diversity.